Pengaruh Word Of Mouth, Harga, Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Masker Merek Sensi Akibat Adanya Pandemi Covid-19 (Studi Kasus Masyarakat Kecamatan Purwoharjo Kabupaten Banyuwangi) - Baha’ul Mu’in; Rois Arifin; M Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe impact of the covid-19 pandemic that has hit all countries in the world, of course, the products that consumers need are products that can prevent and protect themselves from the transmission of covid-19. Mask products are one of the alternative choices of consumers who are most bought at this time. This is a Sensi mask product. This study aims to determine how the influence of word of mouth, price, brand image, and product quality on purchasing decisions.This study uses quantitative methods. The population of this study were consumers of Sensi brand masks in Purwoharjo District, Banyuwangi. The technique of collecting data is by distributing questionnaires. The sample of this research was taken by purposive sampling technique with the Malhotra formula, totaling 125 respondents in the community of Purwoharjo Banyuwangi District. The variables in this study are Word Of Mouth (X1), Price (X2), Brand Image (X3), Product Quality (X4), and Purchase Decision (Y). The data analysis methods used are instrument test, normality test, classical assumption test, multiple linear regression analysis test hypothesis, and test the coefficient of determination with the help of SPSS 20.0 software for windows.The results of this study indicate that word of mouth, price, brand image, and product quality simultaneously or partially have a significant effect on purchasing decisions for Sensi brand masks (a case study of the people of Purwoharjo District, Banyuwangi Regency). Keywords: Word Of Mouth, Price, Brand Image, Product Quality, and Purchase Decision.